ダイ13ジ コウカイ チュウ ニ カンサツ シタ シュヨウ ウミドリ ノ シュツゲン キロク ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 青柳, 昌宏; アオヤナギ, マサヒロ; AOYANAGI, Masahiro (国立極地研究所, 1973)
P(論文) 1. Sea birds were observed during the cruise of the 13th Japanese Antarctic Research Expedition from December 1971 through April 1972. 2. The principal species observed are as follows : 1 species of Family Spheniscidae, 6 species of Family Diomedeidae, 11 species of Family Procellariidae, 2 species of Family Hydrobatidae and 1 species of Family Stereorariidae 21 species in total. 3. The sea birds distribution on the Subantarctic and Antarctic Ocean was found to be considerably depending on the latitude. departmental bulletin paper